ECO FRIENDLY CITRIC ACID-ASSISTED SOL-GEL SYNTHESIS OF HIGH-PURITY NANO SILICA FROM DIENG GEOTHERMAL SLAG: CHARACTERIZATION AND OPTIMIZATION METHOD - Birawidha, David C; Manaf, Azwar; Astuti, Widi; Daulay, Amru; Haryono, Tri; Sari, Yuliana; Suprihatin, Suprihatin (Universitas Mataram, 2025)
Geothermal slag is a by-product of the geothermal power generation process, but its added value is minimal. With a silica content of up to 70%, geothermal slag has potential as a secondary silicon source for battery silicon anode precursors. Usually, the synthesis of nano-silica was carried out through the sol-gel method, in which HCl is usually used as a modifier to regulate the physical and chemical properties of the material. But in this study chose citric acid for modifier agent because it is more environmentally friendly. The challenge of using citric acid is the formation of carbon-based salts that can cause silica blackening if not washed well. Therefore, optimization was done by adjusting the pH to produce high-purity nano-silica. The sol-gel process was carried out by adding 10% NaOH and 5N Citric Acid, with varying pH base conditions from 8 to 11. XRF analysis results showed the highest purity at pH 8. Impurities were still visible based on XRD data, and the formation of nanoparticles was confirmed through morphological analysis using FESEM and TEM where the average particle size formed is between 55 nm.